Systematic Approach to the Trauma Patient in Disaster - Ozkan, Seda; Biberoğlu, Serap (Cerrahpaşa Medical Journal, 2023)
A disaster is an event that consumes the local medical resources necessary to provide comprehensive and definitive medical care in the area where it occurs. In a disaster, it is primarily aimed to provide care to the patients whose situation is the most urgent and who can benefit most from the treatment. Trauma is a leading cause of death worldwide. Traumatic injuries can range from small, isolated wounds to complex injuries involving multiple organ systems. Disaster situations are chaos. In this chaos, the approach to the trauma patient must be in a certain sequence, order, and speed. Injured patients should be evaluated and treated according to their current vital signs, state of consciousness, and mechanism of injury. In order to reduce morbidity and mortality after traumatic injuries, trauma patients should be managed systematically from the scene to the emergency department. Cite this article as: Ozkan S, Biberoğlu S. Systematic approach to the trauma patient in disaster. Cerrahpaşa Med J. 2023;47(S1):47-51.